The mediating effect of organisational resilience and internal preparedness on the relationship between external vulnerabilities and performance - Francis, Godwin; Papadaki, Maria; Saeed, Hamid (2024)
The performance of an organisation is contingent on external and internal business environments. A resilient business process strengthens the stability of the organisation. The underlying study focused on the effect of organisational resilience on business performance under the influence of external vulnerabilities. A survey was conducted, and data were collected from 144 organisations in the UAE. Structural equation modelling was used to test the hypotheses. The findings showed that organisational performance was positively and significantly related to external and internal factors with resilient characteristics and capacities. The relationships between resilient characteristics, resilient capacities, and firm performance were also positive and significant. The mediation results showed an indirect relationship between resilient characteristics and firm performance, and resilient capacities fully mediated this association. The research has contributed to resilience theories, and has also provided a framework to managers and decision makers to achieve greater resilience for better business performance.